Microstrip and printed antenna design - Bancroft, Randy (Raleigh, NC SciTech Publishing, 2009)
The following topics are dealt with: rectangular microstrip antennas; circular microstrip antennas; broadband microstrip antennas; dual-band microstrip antennas; microstrip arrays; and printed antennas.
Electronic reproduction.
Keywords: Microstrip antennas; Antenna arrays; Antennas (Electronics).; Electronic books